2018
DOI: 10.1002/14651858.cd010604.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological interventions for the prevention of insufficiency fractures and avascular necrosis associated with pelvic radiotherapy in adults

Abstract: Pharmacological interventions for the prevention of insu iciency fractures and avascular necrosis associated with pelvic radiotherapy in adults (Review)van den Blink QU, Garcez K, Henson CC, Davidson SE, Higham CE van den Blink QU, Garcez K, Henson CC, Davidson SE, Higham CE. Pharmacological interventions for the prevention of insu iciency fractures and avascular necrosis associated with pelvic radiotherapy in adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 81 publications
0
21
0
2
Order By: Relevance
“…According to the results of the present study, 45.2% of patients with PIF were symptomatic. Treatment is generally conservative, with analgesic administration and rehabilitation ( 33 ). Early diagnosis and treatment may improve pain, immobilization and thus mortality ( 33 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the results of the present study, 45.2% of patients with PIF were symptomatic. Treatment is generally conservative, with analgesic administration and rehabilitation ( 33 ). Early diagnosis and treatment may improve pain, immobilization and thus mortality ( 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…Treatment is generally conservative, with analgesic administration and rehabilitation ( 33 ). Early diagnosis and treatment may improve pain, immobilization and thus mortality ( 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…Two studies have reported effects of bisphosphonates on stress fractures in special disease areas. One analysis found insuffi cient evidence for a positive effect on insuffi ciency fractures and avascular necrosis of the pelvis after pelvic radiotherapy for prostate cancer [28]. Another study, however, reported positive effects of bisphosphonates on stress fractures in patients suffering from Paget´s disease [29].…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that radiation-induced bone loss is a consequence of osteoclastic bone resorption, which the bisphosphonate appeared to have the ability to counteract [ 83 ]. Conversely, the Cochrane Database reviewed two clinical trials examining the effect of bisphosphonate administration in men undergoing pelvis radiation for prostate cancer; insufficient evidence was found to show that bisphosphonate administration prevented radiation-induced bone complications [ 84 ]. Finally, denosumab has been theorized to have radioprotective effects as well, given its function to inhibit osteoclasts [ 18 ].…”
Section: Fracture Preventionmentioning
confidence: 99%